2000
DOI: 10.1182/blood.v95.7.2269
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic doses of granulocyte colony-stimulating factor affect cytokine production by lymphocytes in vitro and in vivo

Abstract: Peripheral blood stem cell (PBSC) transplantation is successful in improving engraftment without increasing acute graft-versus-host disease (GVHD), despite much larger numbers of T cells in unmanipulated PBSCs than in bone marrow grafts. In mouse models and retrospective human studies, granulocyte colony-stimulating factor (G-CSF) therapy has been associated with less acute GVHD. We studied the effect of G-CSF on interferon (IFN)-γ and IL-4 expression in CD4+lymphocytes. CD4+ cells co-cultivated with G-CSF and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
63
0
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 196 publications
(69 citation statements)
references
References 23 publications
4
63
0
2
Order By: Relevance
“…The significant decrease in production of IFN‐γ does directly correlate with a decrease in the cytotoxic activity. So far, it has only been reported that G‐CSF decreases IFN‐γ secretion in CD4+ cells 35 and TNF‐α secretion in PBMNCs 36 . But the secretion of cytokines like IL‐6 or TNF‐α or the chemokine IL‐8 was also down regulated, although not significant in the in vitro assays.…”
Section: Discussionmentioning
confidence: 90%
“…The significant decrease in production of IFN‐γ does directly correlate with a decrease in the cytotoxic activity. So far, it has only been reported that G‐CSF decreases IFN‐γ secretion in CD4+ cells 35 and TNF‐α secretion in PBMNCs 36 . But the secretion of cytokines like IL‐6 or TNF‐α or the chemokine IL‐8 was also down regulated, although not significant in the in vitro assays.…”
Section: Discussionmentioning
confidence: 90%
“…The absence of competing lymphocyte populations could, in this setting, lead to preferential proliferation of oligoclonal T cells in the ALI. Additionally we used GM‐CSF for haematopoietic reconstitution rather than G‐CSF to avoid the T‐helper cell type 2 skewing and T cell hypo‐responsiveness reported with the use of G‐CSF (Sloand et al , ). GM‐CSF also promotes DC differentiation, potentially triggering T cell reactivity against clonal plasma cells over‐expressing CTA in the MRD state.…”
Section: Discussionmentioning
confidence: 99%
“…However, there were two major differences between the related and unrelated donor lymphocyte products studied: 1) all of the unrelated lymphocyte product donors had been given G‐CSF while only about 40% of the related lymphocyte product donors were given G‐CSF and 2) the unrelated donor products had been stored longer before cryopreservation. G‐CSF is known to modulate lymphocyte function and it is possible that G‐CSF–induced changes in CD3+ cells could affect their tolerance of cryopreservation and thawing. It is also possible that prolonged liquid storage of the products before cryopreservation could damage CD3+ cells, thereby reducing their ability to survive the cryopreservation and thawing process.…”
Section: Discussionmentioning
confidence: 99%